The impact of retailers' alliance on manufacturer's profit in a dual-channel structure. Issue 22 (17th November 2017) - Liu, Huihui; Sun, Shuguang; Lei, Ming; Deng, Honghui; Leong, G. Keong
Abstract : When a manufacturer adds a direct sales channel to its existing retail channel, retailers may cooperate with one another to respond to this new competition. Our study develops a Cournot competition model in a dual-channel supply chain consisting of a manufacturer and multiple retailers. In a Stackelberg decision model, the manufacturer first sets the direct sales quantity and wholesale price, and then the retailers decide the order quantities. The results indicate that forming an alliance is not always beneficial for retailers. When direct sales cost is high, there is less likelihood for retailers to collaborate. On the other hand, retailers will form an alliance when direct sales cost is sufficiently low. This will likely reduce the manufacturer's profit. As such decreasing direct sales cost is not necessarily beneficial for the manufacturer because of the retailers' possible collaborative efforts. In addition, the study finds that when demand fluctuation increases or the manufacturer's information accuracy decreases, it is more likely that retailers will form an alliance. After relaxing the assumption of homogeneous retailers, our numerical study validates the possibility of partial alliance. If some retailers' marginal costs are sufficiently high, we could see the formation of a partial alliance.